Production Quality Control Analysis of Harum Manis Using the Six Sigma Method(Case Study: MSME Harum Manis, Lamongan) - Moh. Ferdiansyah; Andika Yuli Heryanto (Universitas Darussalam Gontor, 2023)
The Harum Maniswas a popular traditional food in the 1990s made from sugar, flour, and food coloring. MSME Harum Manis is an MSME that produces harum manis snacks that have been in production since 2012. The author's observations found that the company had problems in its production process, namely, defective products. Types of harum manis product defects are stable fracture, rough fracture, and soft looseness. This research aims to identify the factors that cause product defects, calculate the sigma value in the production harum manis products, and provide suggestions for improving the quality control of harum manis production. The research uses the six sigma method with the concept of DMAIC (define, measure. analyze, improve, and control). The sample used in each data collection is 30 kg. The defect factors for the harum manis product are the slow gulali withdrawal process, the employees being less skilled, the lack of employee training, the addition of flour needs to be more stable, and the production room is now open. The sigma level obtained from MSME Harum Manis in October was 3.4, while in November, a sigma value of 3.28 was obtained. Proposed improvements include conducting training for new and old workers on an ongoing basis, making standard operating procedures (SOP) for workers, making SOP regarding the production process in detail, and closing the production room during production